2009
DOI: 10.12968/bjon.2009.18.8.41811
|View full text |Cite
|
Sign up to set email alerts
|

Using evidence-based practice to address gaps in nursing knowledge

Abstract: Implementing evidence based-practice and research findings into nursing care has been identified as a challenge to nursing staff. This article identifies key barriers to the use of research in the international literature, however, there are limited suggestions as to how to improve this in the clinical arena. This article aims to identify how nurses could optimize the implementation of evidence and research into their clinical care and reviews barriers to implementing and undertaking nursing research, suggesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 23 publications
0
36
0
Order By: Relevance
“…Several barriers have been identified that hinder nurses from getting involved in research activities and key barriers include time constraints, a lack of access to information, a lack of support and limited research knowledge and appraisal skills [42]. Tagney and Haines (2009) argue that too few training opportunities are available for nurses to develop academic skills and propose a practical framework for enhancing evidence-based practice in the nursing environment by ensuring adequate research skills [43]. The authors identify a clear need to improve the "base-line level" of knowledge so that nurses know how to access, interpret and implement evidence to inform practice hence research programmes must be embedded in the nursing education.…”
Section: Discussionmentioning
confidence: 99%
“…Several barriers have been identified that hinder nurses from getting involved in research activities and key barriers include time constraints, a lack of access to information, a lack of support and limited research knowledge and appraisal skills [42]. Tagney and Haines (2009) argue that too few training opportunities are available for nurses to develop academic skills and propose a practical framework for enhancing evidence-based practice in the nursing environment by ensuring adequate research skills [43]. The authors identify a clear need to improve the "base-line level" of knowledge so that nurses know how to access, interpret and implement evidence to inform practice hence research programmes must be embedded in the nursing education.…”
Section: Discussionmentioning
confidence: 99%
“…Learning to critically appraise research is an educational objective within allied health training, with the aim of promoting competent research use in practice (Tagney and Haines, 2009). However, research suggests that there is a discrepancy between the amount of research evidence available and the extent of research use in health care practice (Heiwe et al, 2011); despite its widely acknowledged value (Tagney and Haines, 2009).…”
mentioning
confidence: 99%
“…However, research suggests that there is a discrepancy between the amount of research evidence available and the extent of research use in health care practice (Heiwe et al, 2011); despite its widely acknowledged value (Tagney and Haines, 2009). Research suggests that Newly Qualified Practitioners (NQPs) may enter an area of clinical practice in which evidence-based approaches are infrequently or inconsistently adopted, thus hindering their application of educationally acquired skills (Mooney, 2007;Maben, et al, 2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The reasons generally given for this limited DSI access are a lack of competence with searching tools (1,5) ; organizational factors at the institution where the professional works, namely, a lack of time (1,6) ; the attitudes of the nurses themselves regarding their professional practices based on scientific evidence (1,7,9) ; and the fact that searching for information in a DSI seems like a solitary activity (8) .…”
Section: Descriptoresmentioning
confidence: 99%